Implementation of Participatory Action Research (PAR) In Community Service Program - Khafsoh, Nur Afni; Riani, Nur (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: The purpose of this study is to examine how the Participatory Action Research (PAR) method is applied to the empowerment program and how it is implemented in the Student Community Service Program (KKN). The study aims to see if students can have a positive impact on society and learn from existing social realities, despite the challenges of time and cost limitations. Method: This research uses a qualitative approach and Participatory Action Research (PAR). Data collection was carried out by observing, interviewing, conducting Forum Group Discussions (FGD), and documentation. Data analysis techniques were carried out by reducing, displaying, understanding data, and drawing conclusions. Practical Applications: The research results show that the KKN program can be carried out using the PAR approach by making stages: initial mapping, transects, historical tracing, trends and changes, Venn diagrams, flowcharts, problem and expectation trees, and program strategy analysis. The process is intended to find the basic problem and also try to find a solution according to the problem. Conclusion: From this process, three programs emerged, namely: First, Socialization of environmental awareness; Second, strengthening the waste bank program; Third, FGD between the village government and the waste bank group. These programs address the community’s indifference to environmental concerns and the polarization of illegal landfills in Tambi Village, Kejajar District, Wonosobo Regency, Central Java. The community’s involvement in implementing this program is very important because the PAR method places the community as the subject of the program. This shows that the KKN program can have a positive impact on society when the PAR approach is used.